PERANAN RELIGI DALAM PEMERINTAHAN RAJA JAYAPANGUS (Berdasarkan Data Prasasti) - Ayu Febriyanthi, Ni Luh Gede (Humanis, 2014)
Most of the inscriptions issued by the kings of ancient Bali during one of which contains data related to King Jayapangus belief systems knew as religion. In the reign of King Jayapangus religious cultivation of spiritual values seems so pervasive strong in the joints of the social life of ancient Balinese culture, so it was able survive to the present day. The issues that discussed in this study is what of religious aspects contained in the inscription of the reign of King Jayapangus and role of religious related to the government bureaucracy also the role of religion on social and cultural life of society during the reign of King Jayapangus. This research used a descriptive qualitative analysis of the data collection methods such as literature review, observation and documentation. The theory are used as the basis of religious theory and research is to determine the role of structural functionalism religion in the reign of King Jayapangus. The results that the role of religion in the reign of King Jayapangus was in an effort legitimation of power and abaut as a guide in making policy and role in social life.
Keywords: Roles, Religion, King Jayapangus